On Women Governor Discourse In Yogyakarta Special Regions: A Muhammadiyah View Toward The Constitutional Court No. 88 / PUU-XIV / 2016 - Nofrima, Sanny; Efendi, David; Wijaya, Sakir Ridho; Sjahputra, Hafidz Ridha Try (MUWAZAH: Jurnal Kajian Gender, 2021)
This study aims to answer the discourse of an Islamic organization, namely Muhammadiyah, in response to a female governor in an Islamic society in Yogyakarta who the Indonesian Constitutional Court overthrew. The study used a qualitative descriptive method. The theory used in this research is perception, discourse, leadership, gender, and power. The data in this study are in the form of documents, information based on interviews with Muhammadiyah residents and women activists who are the Governor's discourse. The researcher also uses the Nvivo 12 Plus Application to support this analysis. This study describes that Muhammadiyah as the most influential Islamic group in the Special Region of Yogyakarta does not issue a policy regarding the Governor's discourse and women's resistance, which is relatively closed. This research will be helpful for researchers in the fields of sociology, anthropology, and political science. Also, it will help policymakers to understand their justification for the policy.